The performance of solar bottle bulbs at different interior exposure levels - Wang, C.; How, V.L.; Abdul-Rahman, H. (SAGE Publications (UK and US), 2015)
Different sizes and arrangements of solar bottle bulbs might greatly affect the lighting delivered and there is no general agreement on the best interior bottle exposure levels. This study was undertaken to examine the lighting performance of three prototype solar bottle bulbs and to compare their performance at three different interior bottle exposure levels: one-third, half and two-thirds. A solar bottle bulb made of one 1.5 litre bottle proved to be better than a solar bottle bulb made of three 0.5 litre bottles. In terms of interior bottle exposure levels, the half level performed the best. Some inexplicable phenomena were also observed with recommendations for further study.